OCTN: A Small Transporter Subfamily with Great Relevance to Human Pathophysiology, Drug Discovery, and Diagnostics. (February 2019) - Pochini, Lorena; Galluccio, Michele; Scalise, Mariafrancesca; Console, Lara; Indiveri, Cesare
OCTN is a small subfamily of membrane transport proteins that belongs to the larger SLC22 family. Two of the three members of the subfamily, namely, OCTN2 and OCTN1, are present in humans. OCTN2 plays a crucial role in the absorption of carnitine from diet and in its distribution to tissues, as demonstrated by the occurrence of severe pathologies caused by malfunctioning or altered expression of this transporter. These findings suggest avoiding a strict vegetarian diet during pregnancy and in childhood. Other roles of OCTN2 are related to the traffic of carnitine derivatives in many tissues. The role of OCTN1 is still unclear, despite the identification of some substrates such as ergothioneine, acetylcholine, and choline. Plausibly, the transporter acts on the control of inflammation and oxidative stress, even though knockout mice do not display phenotypes. A clear role of both transporters has been revealed in drug interaction and delivery. The polyspecificity of the OCTNs is at the base of the interactions with drugs. Interestingly, OCTN2 has been recently exploited in the prodrug approach and in diagnostics. A promising application derives from the localization of OCTN2 in exosomes that represent a noninvasive diagnostic tool.